Creation of the image and brand of the enterprise on the basis of marketing as a philosophy of management - Raiko, Diana; Cherepanova, V. O. (Baltija Publishing, 2019)
The modern development of an enterprise is possible only on the basis of marketing since the enterprise is effective only in case of its usefulness for consumers, the relation with which is one of the main marketing functions, i.e., marketing is a philosophy of management. The purpose of the paper is to study the theoretical background and practice of interaction of image and brand of an enterprise on the basis of marketing as a philosophy of management. Methodology. Approbation of the results is presented on the example of business projects for 2017 and 2018 of enterprises with different business scales in Kharkiv and Kharkiv region of Ukraine: small – the Centre for Child Development “Cute Kids”, medium – Association of Confectionery Enterprises “Solodkyi Svit” (“Sweet World”), large – Turboatom JSC, by means of research methods: theoretical generalization, system approach, expert estimation method. Results. The work results are the development of methodological approach to evaluating the effectiveness of the marketing department in the process of business management at the enterprise, taking into account the enterprise value and brand value for large industrial enterprises, the peculiarity of which is the ability to investigate the relationship between the effectiveness of the development of the marketing department (organizational and managerial aspect) and the performance of its divisions (economic aspect) and take into account the identified causal relationships in the process of enterprise activity. The system for evaluating the performance of the marketing department, taking into account enterprise value and brand value, involves two levels of assessment: the first one allows determining its performance in general, that is, the effectiveness of its development, the second one takes into account the specifics of divisions of this department of the enterprise and allows determining their performance according to individual results, that is, the effectiveness of divisions, which is reflected in the basic social and economic performance indicators of the enterprise. The effectiveness of the development of the marketing department is evaluated using the following indicators: development trend ratio, marketing efficiency ratio, management process productivity ratio, division productivity ratio, and executive efficiency ratio. The calculation is based on individual indicators: an integral indicator of the effectiveness of the development of the marketing department, which is calculated by the normalized part of the indicators for additive convolution, taking into account their ratios of significance, and by performance indicators of marketing research division (sales volume, market share, building market strength), the work of the business development division is evaluated using indicators (“corporate image”, “enterprise competitiveness”, “profit”, “consumer readiness”, “partner’s business attractiveness”), communication division (trade turnover, information base update, development of partner relations, brand value), which are interrelated, interdependent, reveal the essence of determining the performance of the marketing department at different angles, allow justifying the adjustment of certain aspects of marketing development at the enterprise, and are calculated as arithmetic mean values of performance indicators of the divisions. Conclusions. Practical approbation of the proposed approach is presented on the example of large industrial enterprise named Turboatom JSC and confirms the practical value of the worked out approach to evaluating the performance of the marketing department in the process of managing the activities of an industrial enterprise, taking into account enterprise value and brand value.
Keywords: image; brand; marketing; enterprise